Problems of using phenol (hydroxybenzene) and parabens as pharmaceutical stabilizers: analysis using machine learning methods - I. Yu. Torshin; O. A. Gromova (Фармакоэкономика)
Background. Phenol and parabens exert bactericidal properties, are relatively low-toxic (in acute toxicity tests) and are used in pharmaceutical, cosmetic and food industries as stabilizers/preservatives for the final product. Despite their widespread use, the long-term toxicological effects of phenol and parabens remain largely unexplored.Objective: To conduct an analysis of the results of basic and clinical studies on chronic toxicity of phenol and parabens.Material and methods. The study included 544 articles found using the query “Preservatives, Pharmaceutical [MeSH Terms] AND Phenol [MeSH Terms]” in the PubMed/MEDLINE biomedical publications database. Methods of topological and metric analysis of big data were applied, developed in the scientific school of Academician of the Russian Academy of Sciences Yu.I. Zhuravlev. Keywords were sorted by empirical Rudakov–Torshin informativeness functionals in the context of combinatorial theory of solvability, followed by combinatorial testing of solvability to find terms with the greatest informativeness.Results. Despite the existence of individual studies on the acute toxicity of phenol and its derivatives (including parabens), the chronic toxicity of phenol and parabens remains poorly understood. This fact is indicated not only by a lack of carefully performed research, but also by the information in safety data sheets supplied by manufacturers of the relevant substances. The associations of phenol and paraben blood levels with certain chronic pathologies in humans have been insufficiently studied. At the same time, the authors of fundamental research, if not “sound the alarm,” then strongly underline the need to conduct large-scale clinical trials on the long-term toxic effects of phenol and parabens. Firstly, this is due to complex estrogen-like effect of phenol and parabens, including (1) effects on estrogen sulfotransferases, (2) direct interactions with estrogen receptors, (3) influence on the expression of steroid receptor genes. Secondly, the available data from fundamental research indicate that phenol/parabens obviously stimulate the the molecular mechanisms of oncogenesis pathophysiology (systematic disturbances in gene expression and corresponding changes in the structure of organ tissues). Thirdly, teratogenic and other toxic effects on the embryo and pregnancy were demonstrated not only in experimental studies (neurotoxicity and teratogenesis in animal models), but also in clinical observations (metabolic disorders in a pregnant woman, including the metabolism of purines and fatty acids beta-oxidation, hyperactivity and/or excess body weight in children, asthma, thyroid dysfunction, etc.).Conclusion. Findings from basic research and selected clinical studies dictate an urgent need to examine the association of phenol/paraben blood levels with chronic pathologies in large-scale clinical trials with cross-sectional and longitudinal design. The lack of indication on toxic effects of parabens and phenols in certain clinical studies may just be an artifact of incorrect data analysis.